Walkability and its association with walking/cycling and body mass index among adults in different regions of Germany: a cross-sectional analysis of pooled data from five German cohorts - Annette Peters; Gavin Rudge; Susanne Moebus; Werner Maier; Nadja Kartschmit; Robynne Sutcliffe; Mark Patrick Sheldon; Karin Halina Greiser; Saskia Hartwig; Detlef Thürkow; Ulrike Stentzel; Neeltje van den Berg; et al. (BMJ Open)
Objectives To examine three walkability measures (points of interest (POI), transit stations and impedance (restrictions to walking) within 640 m of participant’s addresses) in different regions in Germany and assess the relationships between walkability, walking/cycling and body mass index (BMI) using generalised additive models.Setting Five different regions and cities of Germany using data from five cohort studies.Participants For analysing walking/cycling behaviour, there were 6269 participants of a pooled sample from three cohorts with a mean age of 59.2 years (SD: 14.3) and of them 48.9% were male. For analysing BMI, there were 9441 participants of a pooled sample of five cohorts with a mean age of 62.3 years (SD: 12.8) and of them 48.5% were male.Outcomes (1) Self-reported walking/cycling (dichotomised into more than 30 min and 30 min and less per day; (2) BMI calculated with anthropological measures from weight and height.Results Higher impedance was associated with lower prevalence of walking/cycling more than 30 min/day (prevalence ratio (PR): 0.95; 95% CI 0.93 to 0.97), while higher number of POI and transit stations were associated with higher prevalence (PR 1.03; 95% CI 1.02 to 1.05 for both measures). Higher impedance was associated with higher BMI (ß: 0.15; 95% CI 0.04 to 0.25) and a higher number of POI with lower BMI (ß: −0.14; 95% CI −0.24 to 0.04). No association was found between transit stations and BMI (ß: 0.005, 95% CI −0.11 to 0.12). Stratified by cohort we observed heterogeneous associations between BMI and transit stations and impedance.Conclusion We found evidence for associations of walking/cycling with walkability measures. Associations for BMI differed across cohorts.